Social inequalities in health related behaviours in Barcelona. Issue 1 (1st January 2000) - Borrell, Carme; Domínguez-Berjón, Felicitas; Pasarín, M Isabel; Ferrando, Josep; Rohlfs, Izabella; Nebot, Manel
Abstract : OBJECTIVE: This study describes social class inequalities in health related behaviours (tobacco and alcohol consumption, physical activity) among a sample of general population over 14 years old in Barcelona. DESIGN: Cross sectional study (Barcelona Health Interview Survey). SETTING: Barcelona city (Spain). PARTICIPANTS: A representative stratified sample of the non-institutionalised population resident in Barcelona was obtained. This study refers to the 4171 respondents aged over 14. DATA: Social class was obtained from a Spanish adaptation of the British Registrar General classification. In addition, sociodemographic variables such as family structure and employment status were used. As health related behaviours tobacco consumption, alcohol consumption, usual physical activity and leisure time physical activity were analysed. Age adjusted percentages were compared by social class. Multivariate analysis was performed using logistic regression models. MAIN RESULTS: Women in the upper social classes were more likely to smoke, the adjusted odds ratio (OR) for social class V in reference to social class I was 0.36 (95% confidence intervals (95%CI): 0.19, 0.67), while the opposite occurred among men although it was not statistically significant in multivariate analysis. Smoking cessation was more likely among men in the higher classes (OR for class V 0.41, 95%CI: 0.18, 0.90). Excessive alcohol consumption among men showed no differences between classes, while among women it was greater in the upper classes. Engaging in usual physical activity classified as "light or none" in men decreased with lowering social class (OR class IVa: 0.55 and OR class IVb: 0.47). Women of social classes IV and V were less likely to have two or more health risk behaviours (OR for class V 0.33, 95% CI: 0.18, 0.62). CONCLUSION: Health damaging behaviours are differentially distributed among social classes in Barcelona. Health policies should take into account these inequalities.